The Role of Cognitive Potential in Predicting First-Semester GPA of KIP-Kuliah Scholarship Recipients - Prinska Damara Sastri; Recky Recky; Rifqi Farisan Akbar (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to investigate the influence of cognitive potential, measured via the Wonderlic Personnel Test (WPT), on the first-semester Grade Point Average (GPA) of KIP-Kuliah scholarship recipients (Class of 2025) at Universitas Indonesia Membangun (INABA). Using a saturated sampling technique, 94 participants were involved, predominantly female, aged 19, from the Communication Science program, with average IQ scores categorized as